A Development of a Digital Book (Flipbook) for Teaching Explanation Text Writing in Grade 5 Elementary School - Nining Kundari; Kuntoro; Ana Andriyani; Ine Kusuma Aryani (Elementary Teacher Education Program, Majalengka University, 2026)
The low level of explanatory text writing skills among elementary school students has become a significant issue affecting their ability to organize ideas, apply text structures, and use appropriate language features. This study aims to develop a flipbook-based digital book that is valid, practical, and effective in improving the explanatory text writing skills of fifth-grade elementary school students. The research employed a Research and Development (R&D) method using the ADDIE development model, which includes the stages of analysis, design, development, implementation, and evaluation. The research subjects consisted of fifth-grade students at SD Negeri 1 Karangtengah Banjarnegara. Data were collected through observation, interviews, questionnaires, tests, and documentation, while data analysis used both quantitative and qualitative approaches. The results showed that the developed flipbook achieved a validity score with an average of 4.25, categorized as very valid. User responses were in the very good category, with an average score of 4.40 from teachers and 4.35 from students. The implementation of the media was also proven effective in improving students’ writing skills, indicated by an increase in mean scores from 62.40 to 78.60 and the result of the paired sample t-test with a significance value of 0.000. The N-Gain Score of 0.65 indicates a moderate level of improvement. These findings suggest that the flipbook-based digital book can create an interactive and engaging learning environment and contribute to improving students' explanatory text writing skills in elementary schools.